Cancer research: Epidemiological and clinical concepts - Soeripto, Soeripto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1992)
There are differences in background between cancer and other diseases, among others the difference in sex incidence, behaviour, cellular changes, and clinical aspects. Therefore, research on cancer is suggested to be based on cancer epidemiology, basic research, and clinical research. This article discusses the basic principles of cancer research from the point of view of epidemiological and clinical concepts.It is concluded that research in cancer epidemiology must be based on the well-developed cancer registry. The epidemiological and clinical research of cancer must be brought into a comprehensive scheme. It will be useful if basic research is correlated with research in cancer epidemiology. Clinical research must be based on epidemiological and basic research.Key Words: cancer research - cancer registry - cancer epidemiology - oncology - clinical trials